Lactate, Base Excess, and the Pediatric Index of Mortality: Exploratory Study of an International, Multicenter Dataset. Issue 6 (28th February 2022) - Morris, Kevin P.; Kapetanstrataki, Melpo; Wilkins, Barry; Slater, Anthony J.; Ward, Victoria; Parslow, Roger C.
Abstract : OBJECTIVES: To investigate the relationship between ICU admission blood lactate, base excess, and ICU mortality and to explore the effect of incorporating blood lactate into the Pediatric Index of Mortality. DESIGN: Retrospective cohort study based on data prospectively collected on every PICU admission submitted to the U.K. Pediatric Intensive Care Audit Network and to the Australia and New Zealand Pediatric Intensive Care Registry. SETTING: Thirty-three PICUs in the United Kingdom/Republic of Ireland and nine PICUs and 20 general ICUs in Australia and New Zealand. PATIENTS: All ICU admissions between January 1, 2012, and December 31, 2015. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: One hundred twenty-three thousand two hundred fifty-two admissions were recorded in both datasets; 81, 576 (66.2%) in the United Kingdom/Republic of Ireland and 41, 676 (33.8%) in Australia and New Zealand. Of these 75, 070 (61%) had a base excess recorded, 63, 316 (51%) had a lactate recorded, and 60, 876 (49%) had both base excess and lactate recorded. Median lactate value was 1.5 mmol/L (interquartile range, 1–2.4 mmol/L) (United Kingdom/Republic of Ireland: 1.5 [1–2.5]; Australia and New Zealand: 1.4 [1–2.3]). Children with a lactate recorded had a higher illness severity, were more likely to be invasively ventilated, admitted after cardiac surgery, and had a higher mortality rate, compared with admissions with no lactate recorded ( p < 0.001). The relationship between lactate and mortality was stronger (odds ratio, 1.32; 95% CI, 1.31–1.34) than between absolute base excess and mortality (odds ratio, 1.13; 95% CI, 1.12–1.14). Addition of lactate to the Pediatric Index of Mortality score led to a small improvement in performance over addition of absolute base excess, whereas adding both lactate and absolute base excess achieved the best performance. CONCLUSIONS: At PICU admission, blood lactate is more strongly associated with ICU mortality than absolute base excess. Adding lactate into the Pediatric Index of Mortality model may result in a small improvement in performance. Any improvement in Pediatric Index of Mortality performance must be balanced against the added burden of data capture when considering potential incorporation into the Pediatric Index of Mortality model.